Environmental governance: A practical framework to guide design, evaluation, and analysis - Bennett, Nathan J.; Satterfield, Terre (Conservation letters, 2018)
Governance is one of the most important factors for ensuring effective environmental management and conservation actions. Yet, there is still a relative paucity of comprehensive and practicable guidance that can be used to frame the evaluation, design, and analysis of systems of environmental governance. This conceptual review and synthesis article seeks to addresses this problem through resituating the broad body of governance literature into a practical framework for environmental governance. Our framework builds on a rich history of governance scholarship to propose that environmental governance has four general aims or objectives – to be effective, to be equitable, to be responsive, and to be robust. Each of these four objectives need to be considered simultaneously across the institutional, structural, and procedural elements of environmental governance. Through a review of the literature, we developed a set of attributes for each of these objectives and relate these to the overall capacity, functioning, and performance of environmental governance. Our aim is to provide a practical and adaptable framework that can be applied to the design, evaluation, and analysis of environmental governance in different social and political contexts, to diverse environmental problems and modes of governance, and at a range of scales.